Heat Transfer and Friction Factor of Coil-Springs Inserted in the Horizontal Concentric Tubes - Eren, Haydar; Celik, Nevin; Yildiz, Seyba; Durmus, Aydin (Asme, 2010)
The goal of this investigation is to obtain definitive information about the heat transfer characteristics of circular coil-spring turbulators. This is achieved by measuring the wall temperatures on the inner tube of the exchanger. Also the inlet and outlet temperatures and pressure loss of the fluid are measured. These results are parametrized by Reynolds numbers (2500 < Re < 12,000), outer diameters of the springs (D-s=7.2 mm, 9.5 mm, 12 mm, and 13 mm), numbers of the springs (n=4, 5, and 6), and the incline angles of the springs (theta=0 deg, 7 deg, and 10 deg). Additionally, another goal of this work is to quantify the friction factor f of the turbulated heat exchanger system with respect to aforementioned parametric values. As a result, it is found that increasing spring number, spring diameter, and incline angle result in significant augmentation on heat transfer, comparatively 1.5-2.5 times of the results of a smooth empty tube. By the way, friction factor increases 40-80 times of the results found for a smooth tube. Furthermore, as a design parameter, the incline angle has the dominant effect on heat transfer and friction loss while spring number has the weakest effect.
Keywords: heat exchangers; heat transfer